The Rise of the Chapel Wedding in Japan: Simulation and Performance - Fisch, Michael (Japanese journal of religious studies, 2001)
This article draws on the author's experience acting as a priest for Christianstyle chapel weddings in Japan in order to investigate the structure of the ceremony, its ritual value, and the potential reasons behind the growing popularity of the chapel wedding style in contemporary Japan. The chapel ceremony has become increasingly popular in Japan over the course of the last ten years at the expense of the formerly popular Shinto ceremony. The chapel wedding phenomenon is approached using Jean Baudrillard's theory of simulation in order to understand the depth of its ritual function and its role as a commercial product. It is suggested that while the chapel wedding ceremony offers another example of the appropriation and recontextualization of a foreign cultural model into the Japanese cultural repertoire, its sudden rise in popularity marks a wave of dissatisfaction and rejection of previously dominant cultural motifs subsequent to the worsening economic situation.